An Analysis of Inhalation Injury Diagnostic Methods and Patient Outcomes. Issue 1 (January 2016) - Ching, Jessica A.; Ching, Yiu-Hei; Shivers, Steven C.; Karlnoski, Rachel A.; Payne, Wyatt G.; Smith, David J.
Abstract : The purpose of this study was to compare patient outcomes according to the method of diagnosing burn inhalation injury. After approval from the American Burn Association, the National Burn Repository Dataset Version 8.0 was queried for patients with a diagnosis of burn inhalation injury. Subgroups were analyzed by diagnostic method as defined by the National Burn Repository. All diagnostic methods listed for each patient were included, comparing mortality, hospital days, intensive care unit (ICU) days, and ventilator days (VDs). Z -tests, t -tests, and linear regression were used with a statistical significance of P value of less than .05. The database query yielded 9775 patients diagnosed with inhalation injury. The greatest increase in mortality was associated with diagnosis by bronchoscopy or carbon monoxide poisoning. A relative increase in hospital days was noted with diagnosis by bronchoscopy (9 days) or history (2 days). A relative increase in ICU days was associated with diagnosis according to bronchoscopy (8 days), clinical findings (2 days), or history (2 days). A relative increase in VDs was associated with diagnosis by bronchoscopy (6 days) or carbon monoxide poisoning (3 days). The combination of diagnosis by bronchoscopy and clinical findings increased the relative difference across all comparison measures. The combination of diagnosis by bronchoscopy and carbon monoxide poisoning exhibited decreased relative differences when compared with bronchoscopy alone. Diagnosis by laryngoscopy showed no mortality or association with poor outcomes. Bronchoscopic evidence of inhalation injury proved most useful, predicting increased mortality, hospital, ICU, and VDs. A combined diagnosis determined by clinical findings and bronchoscopy should be considered for clinical practice.